Manipulating the processing window of directed self-assembly in contact hole shrinking with binary block copolymer/homopolymer blending - Wu, Zhiyong; Luo, Jiacheng; Li, Luyang; Dong, Qingshu; Zhang, Xiaohui; Li, Zili; Liu, Yadong; Ji, Shengxiang; Li, Weihua; Zhang, Yan; Xiong, Shisheng (iScience, 2024)
Directed self-assembly (DSA) lithography has demonstrated significant potential in fabricating integrated circuits. However, DSA encounters limited processing windows due to the requirement for precise matching between the period of block copolymers (BCPs) and graphoepitaxy templates. We propose a binary BCP/homopolymer blending strategy to manipulate the self-assembly behavior and the processing window of graphoepitaxy DSA in contact hole shrinking. By carefully tailoring the blending rates of poly(methyl methacrylate) (PMMA) with different molecular weights in cylindrical polystyrene-b-poly(methyl methacrylate) (PS-b-PMMA), we manipulate the period and morphology of BCP/homopolymer self-assembly. Specifically, we employ BCP/homopolymer blending to fine-tune the critical dimension (CD) of contact holes with PS-affined topographical templates. Subsequent pattern transferring is achieved by selectively etching defect-free shrinkable cylinders as hard masks. Furthermore, self-consistent field theory (SCFT) simulation was employed to explore the self-assembly of BCP/homopolymer blending in confined cylindrical space and the results were in good consistency with the experimental results. [Display omitted] •Blending manipulating the self-assembly period and morphology•Processing window in graphoepitaxy DSA of BCP/homopolymer for contact hole shrinking•DSA pattern transfer by selectively etching defect-free shrinkable cylinders•The SCFT simulation of self-assembly is in good consistent with experimental results Chemistry; Materials science; Physics